Propagation of longitudinal waves in biological media - Khalifeh, Hasan (Latakia University Journal -Basic Sciences Series, 2013)
إن الهدف من البحث المقدم في هذا العمل هو وضع طريقة عامة لحل مسائل الاهتزازات الطولانية، وحل هذه المسائل بالنسبة لمنظومات قضبانية من مواد مرنة لاخطية وذلك بوجود العامل البيولوجي. لقد استخدمنا معادلات الاهتزازات الطولانية على قضيب من مادة مرنة لاخطية آخذين بالاعتبار وجود العامل البيولوجي، حيث أخذت مادة القضيب لاخطية. وتم حل المسألة من أجل قضيب منتهي الطول. The main goal of the presented research in this paper is to find a general way to solve longitudinal vibration problems. This way must solve these problems in nonlinear elastic bar systems with a biological factor. We applied longitudinal vibration equations in a nonlinear elastic bar with biological factor, the bar material was taken non-linear. and solve the problem in a bar of finite length.